A Synergistic Effect of Lp(a) and GRACE Score on Cardiovascular Risk in Acute Coronary Syndrome Patients Undergoing Percutaneous Coronary Intervention: A Cohort Study From China - Hu, Chengping; Liu, Jinxing; Han, Hongya; Sun, Yan; Cheng, Yujing; Liu, Yan; Gao, Ang; Zhou, Yujie; Zhang, Jianwei; Zhao, Yingxin (Frontiers in Cardiovascular Medicine, 2021)
Obejectives: Lipoprotein(a) [Lp(a)] has been thought as an independent risk factor for atherosclerotic cardiovascular disease (ASCVD). The Global Registry of Acute Coronary Events (GRACE) score is used to predict the risk of death or death/nonfatal myocardial infarction in patients with acute coronary syndromes (ACS). It suggests that there may be a synergism between Lp(a) and the GRACE risk score on predicting cardiovascular events. Accordingly, this study aimed to test the hypothesis that Lp(a) related cardiovascular risk could be significantly modulated by the GRACE risk score in patients with ACS undergoing percutaneous coronary intervention (PCI). Methods: Patients hospitalized with ACS undergoing PCI were enrolled and followed up for 18 months. The primary outcome was the composite of death, nonfatal myocardial infarction, nonfatal stroke and unplanned repeat revascularization. A Cox proportional hazards regression model was used to determine the relationship between Lp(a) and cardiovascular events. Results: A total of 6309 patients were included (age: 60.1±10.06 years, male: 75.2%, BMI: 26.2±10.57 kg/m2). A total of 310 (4.9%) cardiovascular events occurred. When the overall population was stratified by a GRACE score of 91 or less vs. more than 91 and by tertiles of Lp(a), higher Lp(a) was significantly associated with cardiovascular events only when the GRACE score was greater than 91(tertile 2 vs. tertile 1: HR 1.31, 95%CI:0.86-1.98, P = 0.205; tertile 3 vs. tertile 1: HR 1.94, 95% CI:1.32-2.84, P = 0.001; P for trend=0.002). However, no such significant correlation between cardiovascular events and Lp(a) emerged in the case of a GRACE score 91 or less, and there was a significant interaction for cardiovascular events between Lp(a) tertiles and dichotomized GRACE scores (P for interaction＜0.001). Conclusions: In ACS patients undergoing PCI, there was a synergistic effect between the GRACE risk score and on-statins Lp(a) on predicting cardiovascular events. This finding could help us more accurately identify patients who would benefit most from Lp(a)-lowering treatment.